2022
DOI: 10.1038/s41419-022-05026-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of LSECtin in gastric cancer cell adhesion, migration, invasion, and lymphatic metastasis

Abstract: Liver and lymph node sinusoidal endothelial cell C-type lectin (LSECtin) plays an important regulatory role in a variety of diseases, including tumors. However, the underlying mechanism of LSECtin in gastric cancer (GC) remains largely unknown. In our research, LSECtin promoted the adhesion and invasion of GC cells, and was involved in lymphatic metastasis of GC cells. Mechanistically, LSECtin promoted the adhesion, proliferation and migration of GC cells by downregulating STAT1 expression. The circular RNA ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Over the past decades, an increasing number of tissue-and plasma-derived circRNAs have been demonstrated to be associated with the lymphatic metastasis of gastric cancer (23,24). CircRNAs are sometimes used to clarify the regulatory mechanisms of specific molecules involved in the lymph node metastasis of gastric cancer (25). A recent study determined circRNA profiles in cancer-associated fibroblasts (CAFs) and identified that CAF-specific circCUL2 conferred the CAF phenotype on normal fibroblasts and mediated the CAF oncogenic effects by modulating the miR-203a-3p/MyD88/NF-κB/IL6 axis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, an increasing number of tissue-and plasma-derived circRNAs have been demonstrated to be associated with the lymphatic metastasis of gastric cancer (23,24). CircRNAs are sometimes used to clarify the regulatory mechanisms of specific molecules involved in the lymph node metastasis of gastric cancer (25). A recent study determined circRNA profiles in cancer-associated fibroblasts (CAFs) and identified that CAF-specific circCUL2 conferred the CAF phenotype on normal fibroblasts and mediated the CAF oncogenic effects by modulating the miR-203a-3p/MyD88/NF-κB/IL6 axis (26).…”
Section: Discussionmentioning
confidence: 99%
“…According to a pre-clinical study, the binding of LSECtin to LAG-3 in a B16 melanoma model downregulates IFN-γ secretion, thereby blocking T cell immunity. Furthermore, LSECtin plays a role in the invasion and growth of gastric cancer cells, and eventually results in the development of gastric cancer 78 . FGL-1 directly downregulates the secretion of IL-2, thus conveying a negative regulatory signal 79 , whereas Gal-3 binds oncoproteins and elicits tumor cell proliferative effects.…”
Section: Emerging Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Consequently, blockade of circFBXL4-mediated sponging effects on miR-146a-5p-led to reduction in the levels of STAT1 and subsequent upregulation of FN1 and CHD4 ( Fig. 5 ) [ 91 ]. Collectively, these findings indicated that migration and invasion of gastric cancer cells mediated by LSECtin was impaired significantly by overexpression of circFBXL4 or miR-146a-5p depletion.…”
Section: Tumor Suppressive Role Of Stat1mentioning
confidence: 99%